Drug-induced musical hallucination - Bakewell, Brock; Johnson, Michael; Lee, Madison; Tchernogorova, Elizabeth; Taysom, Jesse; Zhong, Qing (Frontiers in Pharmacology, 2024)
Musical hallucination is a rare perceptual phenomenon wherein individuals hear music in the absence of external auditory stimuli. This phenomenon occurs across diverse medical conditions and can be triggered by some drugs. The underlying mechanism of drug-induced hallucination is unknown. This study explores drug-induced musical hallucination through a literature review, aiming to investigate its pathophysiology and potential treatment modalities. A literature search was conducted until January 2023 using databases PubMed, WorldCat, Google Scholar, and DOAJ, with keywords "drugs induced musical hallucination" or "drugs" combined with "musical hallucination." The search yielded 24 articles which met inclusion criteria, encompassing 27 cases. The average patient age was 58.3 years, with 67.9% females. Prevalent conditions among cases included hearing impairments, psychiatric disorders, cancers, and neurodegenerative conditions. Common trigger drugs comprised antidepressants, opioids, anti-Parkinson drugs, ketamine, and voriconazole. Musical hallucination descriptions varied widely, and 6 patients reported concurrent visual hallucinations. The onset of symptoms ranged from 75 minutes to 240 days. Treatment strategies included termination of trigger drugs, dosage reduction, alteration of administration routes or formula, switching to similar drugs, or addition of antidepressants, sedatives, or atypical antipsychotic medications. Musical hallucinations completely disappeared in 24/27 (88.9%) patients but continued in 3/27 (11.1%) patients. The current study concludes that drug-induced musical hallucination may arise from altering neurotransmitter/receptor balance and intricate interactions between trigger drugs and underlying conditions.